Differentiable Mappings of Affine Spaces into Manifolds of m-Planesin a Multidimensional Euclidean Space; Russian Mathematics (Izvestiya VUZ. Matematika); Vol. 53, iss. 11 - Ivlev E. T. Evgeniy Tikhonovich (2009, 2009)
Title screen